Enhancing the Capacitive Storage Performance of Carbon Fiber Textile by Surface and Structural Modulation for Advanced Flexible Asymmetric Supercapacitors. (27th December 2018) - Han, Yi; Lu, Yongzhuang; Shen, Shenghui; Zhong, Yu; Liu, Si; Xia, Xinhui; Tong, Yexiang; Lu, Xihong
Abstract: The exploration of high‐energy anodes with good mechanical properties is highly attractive for flexible asymmetric supercapacitors (ASCs) but challenging. Owing to the excellent conductivity and superior mechanical flexibility, carbon fiber textile (CFT) holds great promise as a substrate/current‐collector for fabricating flexible electrodes. Yet, it is rarely used as a flexible active electrode in terms of its low electrochemical reactivity and small accessible area. In this work, an effective surface and structural modulation strategy is developed to directly tune CFT into a highly active anode for flexible ASCs by creating hierarchical pores and numerous pseudocapacitive oxygenic groups. Arising from large surface and increased active sites, the as‐prepared activated porous CFT (APCFT) electrode not only achieves a large capacitance (1.2 F cm −2 at 4 mA cm −2 ) and fast kinetics but also shows satisfying cycling durability (no capacitance decay after 25 000 cycles). More importantly, an advanced flexible ASC device with an impressive energy density of 4.70 mWh cm −3 is successfully assembled by employing this APCFT as an anode, outperforming most recently reported ASC devices. This dual modification strategy may throw light on the rational design of new generation advanced carbon electrodes for high‐performance flexible supercapacitors. Abstract : An effective surface and structural modulation strategy is developed to directly tune carbon fiber textile into highly active anodes. Benefiting from the hierarchical pores and abundant oxygenic groups, this electrode delivers an areal capacitance of 1.2 F cm −2 and excellent rate capability. Based on this anode, a flexible asymmetric supercapacitors device of 4.70 mWh cm −3 is also demonstrated.